2021
DOI: 10.1093/humrep/deab130.308
|View full text |Cite
|
Sign up to set email alerts
|

P–309 Effectiveness of intrauterine infusion of platelet-rich plasma (PRP) vs. granulocyte colony-stimulating factor (G-CSF) in women with thin endometrium undergoing assisted reproduction

Abstract: Study question To compare the effect of intrauterine infusion of platelet-rich plasma (PRP) and granulocyte colony-stimulating factor (G-CSF) on endometrial thickness, clinical pregnancy rate and live-birth rate. Summary answer According to our research, PRP-therapy has more positive results in pregnancy rates. Nevertheless, there is still limited data to answer all questions completely. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…A total of seven studies were therefore included in the final analysis, yielding a total of 479 patients [12][13][14][15][16][17][18] [Table 2]. 2 publications [16,18] are randomized studies; 6 publications [12][13][14][15]17] are nonrandomized studies. Also we included the forms of administration of PRP and G-CSF in the Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of seven studies were therefore included in the final analysis, yielding a total of 479 patients [12][13][14][15][16][17][18] [Table 2]. 2 publications [16,18] are randomized studies; 6 publications [12][13][14][15]17] are nonrandomized studies. Also we included the forms of administration of PRP and G-CSF in the Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Nayar, et al considered that autologous PRP and G-CSF hold promise in the treatment of women with sub optimal ET for embryo transfer. It would help to reduce the incidence of cycle cancellations and thus help reduce the financial and psychological burden of repeated cancelled cycles [18].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Frozen embryo transfer (FET) has become a common practice in assisted reproductive techniques. Many techniques had been used in intracytoplasmic sperm injection (ICSI) to improve endometrial receptivity [1] but also the embryo quality has an important role in pregnancy occurrence It has been found that embryo cryopreservation increases the cumulative pregnancy rate in ICSI cycles [2]. Zona pellucida (ZP) hardening as a consequence to cryopreservation can impair embryo hatching and in turn lowering the implantation rate [3].…”
Section: Introductionmentioning
confidence: 99%